Pengembangan Sistem Informasi Pengadaan Bahan Baku Berbasis Web - Aulia Putri Muthiya; Tumini Tumini (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
Printec Perkasa II is a manufacturing company engaged in printing and packaging. During the process of procuring this stock of raw materials, PT. Printec Perkasa II still using a manual system in carrying out its operational activities, especially in processing transaction data for recording inventory, which still uses paper inventory forms. With the data processing process which is still manual, there is often a buildup of data, so that the final information about the stock of goods produced is sometimes not in accordance with the physical stock in the warehouse. This information system was created using the PHP programming language and MySQL database. The aim of this research is to design and build a system that can help PT. Printec Perkasa II in controlling the inventory amount of each item appropriately and Implementing inventory applications at PT. Printec Perkasa II so that cooperative members can speed up the production of goods ordering information so that there are no delays in ordering goods.